Efektifitas Metode Role Playing Pada Pembelajaran Pai Terhadap Penanaman Nilai Anti Korupsi Di Smpn 2 Ampek Angkek - Vivi Mavika Mulya; Wedra Aprison (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The background of this research is that some students have not implemented instilling values corruption ​​in PAI learning. Like the dishonest behavior that appears among junior high school students by opening cheat sheets, asking friends. Based on this, the researcher applies the Role Playing method to PAI learning in instilling corruption values. This study also aims to determine the effectiveness of the Role Playing method in instilling anti-corruption values ​​at SMPN 2 Ampek Angkek. The hypothesis in this study is "The Role Playing Method is effective in instilling anti-corruption values ​​in class VIII students of SMPN 2 Ampek Angkek". This type of research is an experiment with the Static Group Comparison research design. The population in this study were all students of class VIII. The sample in this study were students of class VIII.1 as the experimental class and class VIII.2 as the control class. The research data was obtained from the results of a questionnaire on anti-corruption values. The data analysis technique used is the u-test or the Mann-Whitney test. From the Mann-Whitney test, it was obtained that the smallest U count was known -101 which was then compared with the U table with n1= 20 and n2 = 20 (∝) = 5% in the two-party test table, the U table value was 127. It can be concluded that H0 rejected H1 accepted.